VIZIUNEA PLATONICIANĂ MODIFICATĂ ȘI O NOUĂ PERSPECTIVĂ: THE MODIFIED PLATONIC VIEW AND A NEW PERSPECTIVE (Romanian Journal of Analytic Philosophy, 2025)
This paper examines a modified Platonic view, characterized by gauge symmetry and non-Euclidean geometry, as a framework for understanding the laws governing our known Universe. Building upon the work of physicist Lee Smolin, this perspective has also undergone a critical analysis that has provided the basis for a conceptual clarification of the modified Platonic view. As a result, the article proposes a more nuanced approach, termed the approximate, modified Platonic view, which aims to highlight the limitations but also the attractions of Platonism.
Keywords: gauge symmetry; non-Euclidean; modified Platonic view; approximate; Smolin